The Contemporary Medieval in Practice - Lees, Clare A. (UCL Press, 2019)
Contemporary arts, both practice and methods, offer medieval scholars innovative ways to examine, explore, and reframe the past. Medievalists offer contemporary studies insights into cultural works of the past that have been made or reworked in the present. Creative-critical writing invites the adaptation of scholarly style using forms such as the dialogue, short essay, and the poem; these are, the authors argue, appropriate ways to explore innovative pathways from the contemporary to the medieval, and vice versa. Speculative and non-traditional, The Contemporary Medieval in Practice adapts the conventional scholarly essay to reflect its cross-disciplinary, creative subject.